The mystery behind the nostrils – technical clues for successful nasal epithelial cell cultivation - Aydin, Malik; Naumova, Ella A.; Bellm, Aliyah; Behrendt, Ann Kathrin; Giachero, Federica; Bahlmann, Nora; Zhang, Wenli; Wirth, Stefan; Ehrhardt, Anja; Arnold, Wolfgang H.; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Objectives: Research involving the nose reveals important information regarding the morphology and physiology of the epithelium and its molecular response to agents. The role of nasal epithelial cells and other cell subsets within the nasal epithelium play an interesting translational split between experimental and clinical research studying respiratory disorders or pathogen reactions. With an additional technical manuscript including a detailed description of important technical aspects, tips, tricks, and nuances for a successful culturing of primary, human nasal epithelial cells (NAEPCs), we here aim to improve the process of communication between experimentalists and physicians, supporting the purpose of a fruitful work for future translational projects. Methods: Based on previous work on various complex culture models of subject-derived NAEPCs, this additional manuscript harmonizes previously published facts combined with own experiences for a trouble-free implementation in laboratories. Results: A well-designed experimental question is essential prior to the establishment of different NAEPCs culture models. The correct method of cell extraction from the nasal cavity is essential and represent an important basis for successful culture work. Prior enzymatic processing of biopsy specimens, cell culture materials, collagenization procedure, culture conditions, and choice of culture medium are some important practical notes that increase the quality of the culture. Moreover, protocols on imaging techniques including histologic and electron microscopy must be adapted for NAEPC culture. Adapted flow cytometric protocols and transepithelial electrical resistance measurements can add valuable information. Outlook: A successful culturing of NAEPCs can provide an important basis for genetic studies and the implementation of omics-science, which is increasingly receiving broad attention in the scientific community. The common aim of in vitro ‘mini-noses’ will be a breakthrough in laboratories aiming to perform research under in vivo conditions. Here, organoid models are interesting models presenting a basis for translational studies.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Cell culture; Culture models; Modeling; Nasal epithelial cells; Nasal epithelium; Nose